Wafer-level fabrication of 3D nanoparticles assembled nanopillars and click chemistry modification for sensitive SERS detection of trace carbonyl compounds. (20th April 2020) - Cheng, Jie; Liu, Yang; Mao, Haiyang; Zhao, Wenjie; Ye, Yifei; Zhao, Yang; Zhang, Lingqian; Li, Mingxiao; Huang, Chengjun
Abstract: In this work, we develop a new method for fabricating wafer-level gold nanoparticles covered silicon nanopillars (SNPs) combined with surface chemical modification to detect trace level carbonyl compounds based on surface-enhanced Raman scattering (SERS) technique. The SNPs are fabricated with an etching process using nano masks synthesized in oxygen-plasma bombardment of photoresist, and further deposited with gold nanoparticles on the surface, thus forming a 3D 'particles on pillars' nanostructure for sensitive SERS detection. The enhancement factor (EF) of the devices for R6G detection can achieve 1.56 × 10 6 times compared with a flat Si substrate. We also developed an oximation click chemistry reaction procedure by chemically modifying the nanostructures with aminooxy dodecane thiol (ADT) self-assemble modification. The chip is further integrated with a polydimethylsiloxane (PDMS) microfluidic chamber, which allows fast and convenient detection of trace carbonyl compounds in liquid samples. The SERS detection capability was demonstrated by the dropwise addition of fluorescent carbonyl compounds before and after elution. Furthermore, the device was proved with high surface consistency(<70%) for repeated measurement, which has the potential for ppb(parts per billion) level concentration of carbonyl compounds detection.